PENGARUH PERTUMBUHAN EKONOMI, BELANJA MODAL DAN UKURAN PEMERINTAH TERHADAP PENGENDALIAN INTERN (STUDI EMPIRIS PADA KABUPATEN DAN KOTA PROVINSI RIAU TAHUN 2014-2019) - Dini Rahma Devi; Desmiyawati Desmiyawati; Oktari Vera (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the effect of economic growth, capital expenditure and size of local government of internal control. The data used in this study are secondary data. The method used for sample selection was purposive sampling. The number of samples in this study were 66 companies. Hypothesis testing in this study was carried out using the t statistical test. The data analysis technique used in this study is multiple linear regression analysis the statistical product and service solution (SPSS) version 20.0 for windows data processing software program. The results of this study indicate that economic growth and size of local government have a significant effect of internal control. Meanwhile, capital expenditure have no effect of internal control.Keyword : Internal Control, Economic Growth, Capital Expenditure and Size of Local Government